Distribution of Leptospira sp. in livestock and the environment in Kelantan after a massive flood - Abdul Rahman, Mohammad Sabri (2018)
Leptospirosis caused by pathogenic leptospires is a worldwide health problem in animals and humans. Humans become infected through direct contact with infected animals or through indirect contact with contaminated water or soil. Outbreaks usually follow heavy rainfall and flooding, particularly in endemic areas. A cross-sectional study was carried out in Kelantan after a massive flood in 2014. The aims of this study were to determine the prevalence of leptospiral infection in livestock and to detect the presence of leptospires in water and soil in livestock farms after the massive flood. In-house immunoglobulin G enzyme-linked immunosorbent assay (IgG ELISA) using Leptospira sp. local isolate as antigen was also developed in this study. Whole blood, serum, and urine from livestock and water and soil from livestock farms were collected in all 10 districts of Kelantan. Altogether, 1728 serum samples from 1024 cattle, 366 goats and 338 sheep were collected. Serum samples were tested for detection of anti-leptospiral antibody using microscopic agglutination test (MAT). Whole blood samples were obtained from 280 cattle, 239 goats, and 116 sheep. Urine samples were collected from 21 cattle, 4 goats, and 6 sheep. In total, 635 whole blood samples and 31 urine samples were inoculated into semisolid Ellinghausen and McCullough, modified by Johnson and Harris (EMJH) medium containing 5-fluorouracil (5-FU) for isolation of Leptospira sp. The Leptospira sp. isolates were further identified using conventional methods (1M NaCl, 8-azaguanine and 13°C), serology (MAT) and molecular methods (multiplex polymerase chain reaction (mPCR) and DNA sequencing). All whole blood and urine samples were also directly tested using mPCR. Water and soil sample were obtained from 28 livestock farms in Kelantan. The samples comprised of 62 soil samples and 62 water samples. The samples were filtered and inoculated into semisolid EMJH medium containing 5-FU for isolation of Leptospira sp. All isolates were further identified as animal samples mentioned above. In-house IgG ELISA using local isolate of L. kmetyi serovar malaysia strain Bejo-Iso9 as antigen (ELISA-Bejo-Iso9) was developed in this study. One hundred and sixty (160) cattle sera were randomly selected. The selected serum samples comprised of 80 seropositive MAT and 80 seronegative MAT were tested with ELISA-Bejo-Iso9. The performance of ELISA-Bejo-Iso9 was compared with in-house IgG ELISA using reference strain 117123 (hardjobovis) antigen (ELISA-117123) and CUSABIO® commercial ELISA. Microscopic agglutination test (MAT) results revealed that 11.75% (203/1728) of the livestock were seropositive for leptospiral infection. Serum samples from livestock were screened against 17 reference strains of pathogenic Leptospira sp., one reference strain of non-pathogenic Leptospira sp. and one local strain of pathogenic Leptospira sp. The districts of Gua Musang (4.12% ; 72/1728) , Kota Bharu (1.74% ; 30/1728), Kuala Krai (1.22% ; 21/1728) and Tanah Merah (1.10% ; 19/1728) showed the higher distribution of leptospiral antibodies in livestock compared to the other six districts. Those four districts were affected by the flood. Cattle had the highest serological prevalence of 8.39% (145/1728), while goats and sheep had 2.37% (41/1728) and 0.93% (17/1728) respectively. The predominant serovars detected were L. hardjobovis (3.70% ; 64/1728) and L. hebdomadis (2.08% ; 36/1728). There was a statistically significant association (p<0.05) between samples collected from livestock that were exposed to the flood compared to those that were not exposed. This result indicates the potential risk associated between flooding and leptospirosis. Leptospira sp. was only isolated from cattle’s urine in Gua Musang. All whole blood samples were negative for Leptospira sp. There were 14 (11.29% ; 14/124) and seven (5.65% ; 7/124) Leptospira sp. were isolated from soil and water respectively. Direct detection using mPCR showed that 0.63% (4/635) of whole blood and 3.23% (1/31) of urine samples were positive for Leptospira sp. Pathogenic Leptospira sp. were detected in two blood samples and one urine sample of cattle. Non-pathogenic Leptospira sp. were detected in two blood samples of goat. All positive samples were from livestock exposed to the flood. Conventional methods revealed varies in the result and failed to differentiate the isolates into pathogenic and non-pathogenic Leptospira sp. Microscopic agglutination test (MAT) showed that the isolates reacted to L. autumnalis, L. hebdomadis, L. pyrogenes, L. bataviae, L. patoc and L.wolffii. However, mPCR showed that all isolates were non-pathogenic Leptospira sp. Futher identification using DNA sequencing found that, all the isolates were identified as L. wolffii, an intermediate species of Leptospira. The presence of L. wolffii in water, soil and animal provides evidence of transmission of the organism within the environment and animal hosts. The sensitivity and specificity of ELISA-Bejo-Iso9 were 53.75% and 98.75% respectively. The sensitivity and specificity of ELISA-117123 were 73.25% and 98.75% respectively. The sensitivity and specificity of CUSABIO® commercial ELISA were 80.00% and 97.50% respectively. Based on the sensitivity and specificity obtained, it shows that commercial ELISA has good performance compared than both in-house ELISA. In conclusion, this study revealed the role of flooding in the transmission and distribution of leptospires to susceptible livestock and represents a threat to public health. The detection of Leptospira sp. in livestock and environment is needed to ensure necessary action to be taken to minimise the occurrence of the disease after the flood. As leptospirosis is endemic in Malaysia, a very specific test is needed to diagnose leptospirosis. ELISA-Bejo-Iso9 was shown to be specific and may be suitable to use for serological diagnosis of leptospiral infection in livestock.